Wildfires and Tourism in the Mediterranean: Balancing Conservation and Economic Interests - Josef Abrhám; Jana Soukupova; Petr Prochazka (BioResources)
Wildfires have been a recurrent issue in the Mediterranean region due to its hot, dry summers and dense vegetation, exacerbated by human activities and climate change. This paper examines the complex relationship between wildfires and tourism in Southern Europe, focusing on their regional patterns, interactions, and socio-economic impacts. The study identifies key drivers of wildfire incidence, such as climatic conditions, vegetation type, human activity, and topography, and analyzes their implications for the tourism sector. Through a systematic review of the literature, the authors highlight the increased frequency and intensity of fires in the Mediterranean, which have caused significant ecological, economic, and social damage. The research also discusses the regional diversity of fire occurrences, revealing that most large fires are concentrated in Spain, Portugal, Greece, Italy, France, and Croatia, among the most popular tourist destinations. The impact of wildfires on tourism is multifaceted. At the same time, they decrease the attractiveness of affected areas, leading to reduced visitor numbers and economic losses. The paper suggests that effective fire management and prevention strategies, including public awareness, sustainable tourism practices, and international cooperation, are essential to mitigate the adverse effects of wildfires. It calls for integrating risk management into tourism development plans to enhance the resilience of Southern European destinations to future fire events.